Pulmonary functional imaging: qualitative comparison of fourier decomposition MR imaging with SPECT/CT in porcine lung - Bauman, Grzegorz; Lützen, Ulf; Ullrich, Mathias; Gaass, Thomas; Dinkel, Julien; Elke, Gunnar; Meybohm, Patrick; Frerichs, Inéz; Hoffmann, Beata; Borggrefe, Jan; Knuth, Hans-Christian; Schupp, Jasper; et al. (Radiology, 2011)
Purpose - - To compare unenhanced lung ventilation-weighted (VW) and perfusion-weighted (QW) imaging based on Fourier decomposition (FD) magnetic resonance (MR) imaging with the clinical reference standard single photon emission computed tomography (SPECT)/computed tomography (CT) in an animal experiment. - - Materials and Methods - - The study was approved by the local animal care committee. Lung ventilation and perfusion was assessed in seven anesthetized pigs by using a 1.5-T MR imager and SPECT/CT. For time-resolved FD MR imaging, sets of lung images were acquired by using an untriggered two-dimensional balanced steady-state free precession sequence (repetition time, 1.9 msec; echo time, 0.8 msec; acquisition time per image, 118 msec; acquisition rate, 3.33 images per second; flip angle, 75°; section thickness, 12 mm; matrix, 128 × 128). Breathing displacement was corrected with nonrigid image registration. Parenchymal signal intensity was analyzed pixelwise with FD to separate periodic changes of proton density induced by respiration and periodic changes of blood flow. Spectral lines representing respiratory and cardiac frequencies were integrated to calculate VW and QW images. Ventilation and perfusion SPECT was performed after inhalation of dispersed technetium 99m (99mTc) and injection of 99mTc-labeled macroaggregated albumin. FD MR imaging and SPECT data were independently analyzed by two physicians in consensus. A regional statistical analysis of homogeneity and pathologic signal changes was performed. - - Results - - Images acquired in healthy animals by using FD MR imaging and SPECT showed a homogeneous distribution of VW and QW imaging and pulmonary ventilation and perfusion, respectively. The gravitation-dependent signal distribution of ventilation and perfusion in all animals was similarly observed at FD MR imaging and SPECT. Incidental ventilation and perfusion defects were identically visualized by using both modalities. - - Conclusion - - This animal experiment demonstrated qualitative agreement in the assessment of regional lung ventilation and perfusion between contrast media-free and radiation-free FD MR imaging and conventional SPECT/CT. - - © RSNA, 2011 - - Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11102313/-/DC1